Analysis of Road Geometrics with ASSHTO Method (Solo–Yogyakarta–NYIA Kulon Progo Toll Road Section 1 Package 1.1 Solo – Klaten (STA 0+000 – 22+300) - Rahayu, Yayuk Sri; Rifai, Andri Irfan; Taufik, Muhammad (DAS Institute, 2022)
To support National Economic Development and the development and improvement of economic activities in Java, the Solo-Yogyakarta-Nyia Kulon Progo Toll Road Section I Package 1.1 Solo – Klaten (STA 0+000 - 22+300) was built. Here the contractor is PT Adhi Karya (Persero) Tbk. This corridor has a strategic role in the Java Island toll road network system. The research on some roads is to make horizontal alignments using the manual method, which will be compared with secondary data on the Kartasura access ramp. In the research and discussion, it can be concluded that there are two horizontal alignment curves consisting of 2 SCS bends in planning. At the Spiral Circle Spiral bend, there is a difference in the parameters Lc and Lt of -27,878 m and TS of -15,956, while the other parameters Xs, Ys, K, and Es are the same. AutoCAD® Civil 3D is considered more effective in geometric road planning because it helps the process of planning drawings simultaneously, making the planning process easier and faster. Using manual calculations has a greater risk, such as arithmetic errors and inaccuracies, and requires a longer time.